Penguatan Usahatani dan Tata Kelola Hukum Organisasi KWT Ratu Nahrasiyah Desa Bendosewu - Hindiawati, Wahyu; Rahayu, Yekti Sri; Muddarisna, Nurul (Universitas Tribhuwana Tunggadewi Malang, 2023)
The Ratu Nahrasiyah Women's Farmers Group (KWT) was recently founded with a simple organizational structure due to a lack of insight into the law in organizing. This is an obstacle in the continuity of the organization at KWT. One of the programs that is a priority for KWT is the use of KWT members' home land by cultivating vegetables in the context of food security at the household level. The obstacle faced by most KWT members is that the vegetable plants they cultivate cannot grow optimally. The solution offered is to improve the skills of KWT members in crop production in home gardens and provide assistance regarding the law and legality of an organization to strengthen the knowledge and insight of KWT members in running the organization. The implementation method is through training, mentoring and practice for KWT members. Training and assistance in plant production by creating vegetable cultivation demonstration plots. Training and assistance in managing organizations as well as understanding the basics of organizational law. The results obtained from training in vegetable cultivation techniques for KWT members are an increase in the knowledge and skills of KWT members in vegetable production. Most of the harvest is sold within the KWT member area, so that the turnaround of small-scale businesses has been successfully implemented. The result of training and assistance in organizational governance is that KWT administrators and members are able to prepare basic budgets/household budgets. Increasing the active role of KWT members in organizations is important for the sustainability of the existence of an organization.ABSTRAKKelompok Wanita Tani (KWT) Ratu Nahrasiyah belum lama didirikan dengan struktur organisasi yang sederhana karena minimnya wawasan tentang hukum dalam berorganisasi. Hal ini menjadi kendala dalam kelangsungan organisasi di KWT. Salah satu program yang menjadi prioritas KWT adalah pemanfaatan lahan rumah para anggota KWT dengan budidaya sayuran dalam rangka ketahanan pangan di tingkat rumah tangga. Kendala yang dihadapi sebagian besar anggota KWT adalah tanaman sayuran yang dibudidayakan tidak dapat tumbuh optimal. Solusi yang ditawarkan yaitu meningkatkan skill anggota KWT dalam produksi tanaman di lahan pekarangan dan memberikan pendampingan tentang hukum dan legalitas suatu organisasi untuk memperkuat pengetahuan dan wawasan anggota KWT dalam menjalankan organisasi. Metode pelaksanaan melalui pelatihan, pendampingan, dan praktek kepada anggota KWT. Pelatihan dan pendampingan produksi tanaman dengan pembuatan demoplot budidaya sayuran. Pelatihan dan pendampingann mengelola organisasi serta pemahaman dasar-dasar hukum berorganisasi. Hasil yang diperoleh dari pelatihan teknik budidaya sayuran kepada anggota KWT adalah peningkatan pengetahuan dan keterampilan anggota KWT dalam produksi tanaman sayuran. Sebagian besar hasil panen dijual di lingkungan anggota KWT, sehingga perputaran usaha skala kecil telah berhasil dilaksanakan. Hasil dari pelatihan dan pendampingan tata kelola organisasi adalah pengurus dan anggota KWT mampu menyusun anggaran dasar/anggaran rumah tangga. Peningkatan peran aktif anggota KWT dalam berorganisasi penting untuk keberlanjutan berdirinya sebuah organisasi